The Effect of Electricity Consumtion, FDI, and Unemployment on Economic Growth in Indonesia 1990-2021 - Rahmansyah, Adi; Yuliawan, Dedy; Gunarto, Toto (Revenue Journal: Management and Entrepreneurship, 2024)
The traditional economic growth hypothesis was created by experts known as the old economist analysts, pioneered by Adam Smith, Robert Malthus, David Richardo, and John Stuart Plant. Given the traditional hypothetical assumptions, economic development is influenced by several variables, including the number of workers seen from the population, the amount of capital, geographical area, and technological development. Economic growth displays how monetary applications increase income or payments for a local area from one period to another. The economic case in Indonesia is still happening now; looking at what aspects affect economic growth, this study examined the variables of Electricity Consumption, FDI, and Unemployment. This exploration uses time series data regression, quantitative methods, and secondary data from the Ministry of Energy and Mineral Resources (MEMR), Central Bureau of Statistics (BPS), and World Development Indicator data from 1990-2021. The data is examined using Eviews 12 software. The experimental results show that the variables of electricity consumption and FDI affect economic growth in Indonesia positively and significantly, while unemployment affects economic growth in Indonesia negatively and significantly for the period 1990-2021.